E-Module as Learning Media to Improve Management Skills of Village-Owned Enterprises (BUMDes): Preliminary Study - Wibowo, Ari; Sumaryati, Sri; Sudiyanto, Sudiyanto (Universitas Sebelas Maret, 2023)
The world becomes more connected and information technology develops quickly, good management skills are the main key in managing village-owned enterprises (BUMDesa) so that they can develop and compete in an increasingly competitive market. This study aimed to analyze the needs of e-modules that are used to improve the management skills of village-owned enterprises. This research was descriptive exploratory research with a sample of 74 respondents. The results of the study indicate the need for e-modules based on indicators of preference and reasons for respondents using digital media for management learning. Respondents assumed that in improving BUM-Des management skills it would be more practical to create content in the form of digital media. A study of student survey data revealed that re-spondents needed more digital teaching materials in the form of modules in order to support their learning activities. The results of this study are ex-pected to be a reference for the development of e-modules that can support the improvement of participants' skills.